Morphometric grading of osteoarthritis by optical coherence tomography — An ex vivo study. Issue 10 (3rd July 2014) - Nebelung, Sven; Marx, Ulrich; Brill, Nicolai; Arbab, Darius; Quack, Valentin; Jahr, Holger; Tingart, Markus; Zhou, Bei; Stoffel, Marcus; Schmitt, Robert; Rath, Björn
Abstract Optical Coherence Tomography (OCT) yields microscopic cross‐sectional images of cartilage in real time and at high resolution. As yet, comprehensive grading of degenerative cartilage changes based on OCT has rarely been performed. This study investigated the potential of quantitative OCT using algorithm‐based image parameters such as irregularity (OII – Optical Irregularity Index), homogeneity (OHI – Optical Homogeneity Index) and attenuation (OAI – Optical Attenuation Index) in the objective grading of cartilage degeneration. Therefore, OCT was used to image and assess 113 human osteochondral samples obtained from total knee replacements. Processing included the analysis of OII (by calculation of the standard deviation with regards to a fitted surface), of OHI (by edge detection of tissue signal changes) and of OAI (by analysis of relative imaging depth). Additionally, samples were subject to macroscopic (Outerbridge grading), biomechanical (elastic stiffness), qualitative OCT and histological evaluation (Modified Mankin grading). Significant correlations were found between all outcome measures. OII and OHI were effective in assessing cartilage surface, integrity and homogeneity, while OAI could discriminate between unmineralized and mineralized cartilage, respectively. Therefore, quantitative OCT holds potential as a diagnostic tool for more reliable, standardized and objective assessment of cartilage tissue properties. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1381–1388, 2014.